The Construction of Islamic Inheritance Law: A Comparative Study of the Islamic Jurisprudence and the Compilation of Islamic Law - Mursyid Djawas; Khairuddin Hasballah; Soraya Devy; Muntasir A Kadir; Yusfriadi Abda (Institut Agama Islam Negeri Batusangkar, 2022)
This article discusses the construction of inheritance law, a comparison between fiqh (Islamic Jurisprudence) and the Compilation of Islamic Law (KHI). This is a normative juridical legal study using a comparative legal approach and the theory of existence as an analytical tool. This article concludes that the fiqh rules regarding inheritance law are based on the understanding of the Qur’an and hadith based on legal construction influenced by the Arabic social and cultural order. This suggests that KHI regulates inheritance law in accordance with the socio-cultural conditions of Indonesian society. The construction of inheritance law in fiqh has both similarities and differences with KHI. The similarity between fiqh inheritance law and KHI is that respectively rely on the Qur’an and hadith as mashadir al-ahkam. Meanwhile, the difference lies in the social reality and the cultural structures of the developing community which affect the two legal systems. The Arab society is patrilineal in its kinship system, whereas in Indonesia it is more bilateral, as a result, the distribution of inheritance tends to be different. Next, when it is seen from the point of view of the existence of this law in Indonesia, the fiqh inheritance law and inheritance law based on KHI still exist. Islamic jurisprudence is recognized as an integral part and raw material for the formation of national law in Indonesia.